Development of Learning Media Based on Androidin Basic Algorithm and Programming Course for Students Grade X of Nasional Berbah Vocational High School - Irfan, R; Wulandari, A (Journal of physics. Conference series, 2019)
The purpose of research are develop Basic Algorithm and Programming for student grade X of National Berbah Vocational High School Application on Android-based learning media and knowing the feasibility of the Android-based learning media. The research use ADDIE as development model. The result of the development is an Android Application that contains material, sample of program, video, and evaluation on learning and can use for self learning or in class. The product has been tested for feasibility based on the assessment of media experts is 95.34% with the category "Very Feasible", the assessment of material experts is 88.6% with categories "Very Feasible" and product testing by students with final result feasibility is 82.47% so that the learning media is very feasible to be used in the learning of Basic Algorithm and Programming in grade X of Nasional Berbah Vocational High School.